Analytical Channel Estimation Approach For OFDM System Based On Near-Optimal Dft-Based Channel Estimator With Leakage Nulling - D. Vijayakumar Reddy, M. Gowtham Reddy, (International Journal of Engineering and Computer Science, 2015)
Although tremendous progress has been made on the past years on channel estimation in ofdm systems still it is considered as area of concern in wireless communication. A novel channel estimation technique with virtual sub carriers is proposed in this work namely a low-complexity but near-optimal DFT-based channel estimator with leakage nulling is proposed for OFDM systems using virtual subcarriers. The flow of the proposed approach is initially starts with time-domain (TD) index set estimation considering the leakage effect then followed by low-complexity TD post-processing to suppress the leakage. The proposed channel estimator approach outperforms the existing channel estimators in terms of efficiency and performance. Finally the performance and complexity of the proposed algorithm are analyzed by simulation results.